Пошаговое объяснение:
х + у = 6
х² - 2у = -13
х = 6 - у
1)
(6 - у)² - 2у = -13
36 - 12у + у² - 2у = -13
у² - 14у + 36 = -13
у² - 14у + 36 + 13 = 0
у² - 14у + 49 = 0
(у - 7)² = 0
у - 7 = 0
у = 7
2)
х = 6 - 7
х = -1
Ответ: (-1; 7)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Пошаговое объяснение:
х + у = 6
х² - 2у = -13
х = 6 - у
х² - 2у = -13
1)
х² - 2у = -13
(6 - у)² - 2у = -13
36 - 12у + у² - 2у = -13
у² - 14у + 36 = -13
у² - 14у + 36 + 13 = 0
у² - 14у + 49 = 0
(у - 7)² = 0
у - 7 = 0
у = 7
2)
х = 6 - у
х = 6 - 7
х = -1
Ответ: (-1; 7)